Analisis Tanggapan Pengemudi Ojek Online terhadap Penerapan E-Tilang di Kota Palembang 2024 - Otariyani, Ayu; Nofrima, Sanny; Febriyanti, Doris (Penerbit Goodwood, 2025)
Purpose: This study aims to deeply analyze the responses of online motorcycle taxi drivers to the implementation of E-Tilang (electronic ticketing) in Palembang City in 2024, by identifying their perspectives, attitudes, and experiences with the system. Methodology: A qualitative approach was used to gain in-depth insight. Data collection methods included field observations, in-depth interviews with drivers, questionnaires to capture broader views, and supporting documentation to strengthen the findings. Results: The implementation of E-Tilang has increased awareness of and compliance with traffic regulations among online motorcycle taxi drivers, mainly because of concerns over sanctions that could affect their income and reputation. However, challenges remain, such as the lack of socialization of incentives, limited driver involvement in policymaking, and the need for better education on the benefits of the system. A more inclusive and communicative approach is essential to ensure the long-term success of E-Tilang in promoting safer and more orderly traffic. Conclusion: E-Tilang in Palembang effectively improved traffic compliance among online motorcycle taxi drivers owing to concerns over penalties. To enhance its impact, better outreach, driver involvement, and education are required. An inclusive approach will support safer and more orderly traffic. Limitations: The short research duration and varying respondent understanding may have influenced the accuracy of the responses. Contribution: This study provides valuable insights for improving e-ticketing policies and serves as a reference for future academic research on traffic law enforcement.